Left Ventricular Strains and Myocardial Work in Adolescents With Anorexia Nervosa - Paysal, Justine; Merlin, Etienne; Terral, Daniel; Chalard, Aurélie; Rochette, Emmanuelle; Obert, Philippe; Nottin, Stéphane (Frontiers in Cardiovascular Medicine, 2022)
Background Anorexia nervosa (AN) is accompanied by bradycardia, low blood pressure (BP) and cardiac morphological remodeling. Systolic and diastolic functions are relatively preserved when assessed by standard ultrasound methods. However, novel advances based on speckle tracking echocardiography (STE), that could detect subtle and early alterations of left ventricular (LV) function, remained poorly used in AN patients. Objective The aim of this study was to assess the cardiac function of AN patients by evaluating LV myocardial strains, myocardial work (MW) and LV mechanical dispersion. We hypothesized that LV strains and global myocardial work would be decreased and LV twisting mechanisms enhanced to preserve the systolic function. Methods Fifty-nine adolescents including 26 women AN patients (14.6 ± 1.9 yrs. old) with a mean duration of AN of 19 ± 9 months and 33 controls (14.1 ± 2.0 yrs. old) underwent STE to assess LV morphology and myocardial regional strains. Results The global longitudinal strain (GLS) was higher in AN patients compared to controls (−18.8 ± 2.0 vs. −16.9 ± 2.8%, p = 0.006). The area under the pressure-strain loop, representing the global MW was not altered but was shifted to the left and downwards in AN patients, due to their lower BP and higher GLS. Intraventricular mechanical dispersion was similar in both groups. Circumferential strains, twisting/untwisting mechanics were preserved. Conclusion Our results strongly support that the cardiac morphological remodeling observed in our AN patients was associated with normal ventricular regional myocardial functions. Only GLS was higher in AN patients, but its clinical significance remains to be demonstrated.